Utilizing Data Systems to Develop and Monitor Occupational Health Programs in a Large Canadian Hospital - Yassi, A. (Methods of Information in Medicine, 1998)
With rapid change in health care requiring greater emphasis on productivity and quality management, occupational health hazards in hospitals have been receiving increasing recognition, now not only focusing on controlling infection, but also on chemical, physical, mechanical as well as psychosocial hazards. Reducing costly time loss from musculoskeletal injuries is a particular imperative. The Department of Occupational and Environmental Medicine at Winnipeg's Health Sciences Centre, developed databases to help priorize, monitor and improve occupational health programs for its 6,000 employees. Risk assessment/risk management models were adopted to identify hazards, quantify risks and priorize intervention. Using the databases permitted the targeting of groups requiring immunization, resulting in increased coverage. New safety products were introduced and found to be cost-beneficial. A return-to-work post-injury program was particularly cost-beneficial. Over the five years following the implementation of occupational health programs, workers' compensation assessment reductions resulted in savings of more than half-a-million dollars annually. The databases were invaluable in affecting these changes.
Keywords: Occupational Health; Program Evaluation; Work Injuries